2005
DOI: 10.1111/j.1944-9720.2005.tb02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinguistic Variables in Advanced Second Language Reading: Learners' Self-Assessment and Enjoyment

Abstract: The present study on second language (L2) reading and individual difference variables (IDVs) examines learners' self‐assessed ability level and enjoyment and the effects of these factors on two different measures of comprehension. The investigation controls for topic familiarity differences by gender and the study utilizes the authentic short story Aniversario by Luis Romero (Virgillo, Friedman, & Valdivieso, 1998). During regular class period, 88 participants from advanced grammar courses completed the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
3
34
0
1
Order By: Relevance
“…In line with previous research suggestions (Baker & Wigfield, 1999;Brantmeier, 2005;Taboada, Tonks, Wigfield, & Guthrie, 2009;Takase, 2007;Wigfield & Guthrie, 1997), this study revealed that intrinsic motivation and avoidance were significantly related to reading proficiency for non-English majors group. Such relationships are also consistent with a claim in the field of general L2 motivation that intrinsic motivation is an important factor for L2 achievement (e.g., Csizér & Dörnyei, 2005;Kim, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous research suggestions (Baker & Wigfield, 1999;Brantmeier, 2005;Taboada, Tonks, Wigfield, & Guthrie, 2009;Takase, 2007;Wigfield & Guthrie, 1997), this study revealed that intrinsic motivation and avoidance were significantly related to reading proficiency for non-English majors group. Such relationships are also consistent with a claim in the field of general L2 motivation that intrinsic motivation is an important factor for L2 achievement (e.g., Csizér & Dörnyei, 2005;Kim, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Participants also reported accurate ability levels. Brantmeier (2005) found that levels of self-assessed abilities positively correlated with levels of enjoyment. These investigations lend support to the hypothesis that self-assessment can be accurate for placement.…”
Section: Self-assessment Questionnairementioning
confidence: 96%
“…However, relatively few studies have reported on the utility of strategy use on various levels of reading comprehension (Brantmeier, 2005). Another crucial significance of this research is paving the way for the learners to figure out IBT tests and tasks that technology is a prerequisite device to accomplish, since they apply technology to enhance their ability in the reading skill.…”
Section: Significance Of the Studymentioning
confidence: 99%